Diversity, Ecology, and Prevalence of Antimicrobials in Nature - Mullis, Megan M.; Rambo, Ian M.; Baker, Brett J.; Reese, Brandi Kiel (Frontiers in Microbiology, 2019)
Microorganisms possess a variety of survival mechanisms, including the production of antimicrobials that function to kill and/or inhibit the growth of competing microorganisms. Studies of antimicrobial production have largely been driven by the medical community in response to the rise in antibiotic-resistant microorganisms and have involved isolated pure cultures under artificial laboratory conditions neglecting the important ecological roles of these compounds. The search for new natural products has extended to biofilms, soil, oceans, coral reefs, and shallow coastal sediments; however, the marine deep subsurface biosphere may be an untapped repository for novel antimicrobial discovery. Uniquely, prokaryotic survival in energy-limited extreme environments force microbial populations to either adapt their metabolism to out-compete or produce novel antimicrobials that inhibit competition. For example, subsurface sediments could yield novel antimicrobial genes, while at the same time answering important ecological questions about the microbial community. This review will include surveying natural products and putative antimicrobial production from environmental ecosystems and shed light on the use of antimicrobial compounds in ecological competition.